The Effect of Individual and Organizational Orientation on Supply Chain Management (Study on Metal Processing MSME in Tegal) - Waskito, Kukuh Rekso; Nursyamsiah, Siti (Management Analysis Journal, 2022)
This study aimed to determine the effect of individual supply chain orientation and organizational supply chain orientation on supply chain management. The subjects in this study were 100 companies engaged in metal processing located in the Tegal area, Central Java. Sources of data from this study were obtained by using a questionnaire distributed to owners and employees of metal processing companies. The data analysis method in this study uses SEM (Structural Equiting Modeling) with the help of PLS (Partial Last Square) software. The results of this study indicated that individual SCO had a positive effect on organizational SCO. Organizational SCO had 3 variables, namely human resource, organizational design and information technology. Human resource for SCO had a positive effect to SCM strategic, organizational design for SCO took effect on strategic SCM and information technology took effect on SCM strategy. Then further research results were human resource for SCO had no effect on SCM operation, organizational design for SCO had no effect on operational SCM and the last one was technology information took effect on SCM operations. The final result was strategic SCM had a significant effect on operational SCM. This study broadened the understanding of the social and behavioral elements of SCM by classifying SCOs into individual SCOs and organizational SCOs.